2015
DOI: 10.1111/bjhp.12154
|View full text |Cite
|
Sign up to set email alerts
|

Health coaching to prevent excessive gestational weight gain: A randomized‐controlled trial

Abstract: What is already known on the subject? Designing interventions to address gestational weight gain (GWG) continues to be a challenge. To date, health behaviour change factors have not been the focus of GWG interventions. What does this study add? Our health coaching (HC) intervention did not reduce GWG more so than education alone (EA). There was an intervention effect on readiness and importance to achieve healthy GWG. Yet there were no group differences regarding confidence to achieve healthy GWG post-interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 67 publications
3
55
0
Order By: Relevance
“…Similar to our study, significant differences in delivery and infant birth outcomes were not found between intervention and control groups in the German pregnancy lifestyle counseling study [34] or between the health coaching and education alone groups in the Australian study [33]. Likewise, no differences in adverse birth outcomes were found in the active lifestyle pregnancy intervention for Latina women [35] or the Swedish study [32], although both studies indicated they were not powered to detect differences between treatment groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to our study, significant differences in delivery and infant birth outcomes were not found between intervention and control groups in the German pregnancy lifestyle counseling study [34] or between the health coaching and education alone groups in the Australian study [33]. Likewise, no differences in adverse birth outcomes were found in the active lifestyle pregnancy intervention for Latina women [35] or the Swedish study [32], although both studies indicated they were not powered to detect differences between treatment groups.…”
Section: Discussionsupporting
confidence: 87%
“…In a Swedish study, the proportions of pregnant women who exceeded IOM recommendations for GWG did not differ between the low cost intervention (recommended GWG, weight gain monitoring, and prescribed exercise) and standard maternity care groups [32]. Likewise, no intervention effect was found for weight gained during pregnancy or excessive GWG in a two-armed health coaching and education study conducted with pregnant Australian women [33]. In contrast, a significantly lower proportion of German women receiving lifestyle counseling (recommended GWG, weight gain monitoring, and diet and exercise goal setting and monitoring) exceeded IOM recommendations as compared to the standard prenatal care control group [34].…”
Section: Discussionmentioning
confidence: 99%
“…A multidimensional survey was developed for this study based on an existing survey34 and components from four validated surveys 32,3537. The survey explored five major dimensions using a total of 109 items.…”
Section: Methodsmentioning
confidence: 99%
“…Several reviews have attempted to discern effective BCTs from GWG interventions, with provision of information on the consequences of behaviour to the individual, motivational interviewing, self-monitoring of behaviour, providing rewards contingent on successful behaviour (Hill et al, 2013a), and goal setting (Brown et al, 2012) potentially useful strategies to help women achieve optimal GWG. It is interesting to note that despite the inclusion of 11 BCTs in HIPP (see Skouteris et al, 2015), including BCTs that have previously been found to be effective, efficacy was not established in this study.…”
Section: Discussionmentioning
confidence: 71%
“…The HCA model of HC draws on constructs (e.g., self-efficacy, outcome expectancies, cognitive factors, readiness) from several health behaviour change theories and principles (Gale, 2010). In order to facilitate comparison with future similar studies, behaviour change techniques (BCTs) were identified (see Skouteris et al, 2015).…”
Section: Health Coaching Interventionmentioning
confidence: 99%